On Bornivorous Set - Fatima Kamil Majeed Al-Basri (Al-Qadisiyah Journal of Pure Science, 2017)
In this paper, we introduce the concept of the bornivorous set and its properties toconstruct bornological topological space .Also, we introduce and study the propertiesrelated to this concepts like bornological base, bornological subbase , bornologicalclosure set, bornological interior set, bornological frontier set and bornological subspace